2008
DOI: 10.1101/lm.998508
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal odor-shock conditioning alters the neural network involved in odor fear learning at adulthood

Abstract: Adult learning and memory functions are strongly dependent on neonatal experiences. We recently showed that neonatal odor-shock learning attenuates later life odor fear conditioning and amygdala activity. In the present work we investigated whether changes observed in adults can also be observed in other structures normally involved, namely olfactory cortical areas. For this, pups were trained daily from postnatal (PN) 8 to 12 in an odor-shock paradigm, and retrained at adulthood in the same task. 14 C 2-DG au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
43
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 91 publications
9
43
0
2
Order By: Relevance
“…COA is supported by a basic network, including olfactory areas, the basolateral amygdala, and the orbitofrontal cortex An increasing amount of findings show that the first stages of olfactory processing, the olfactory bulb and the piriform cortex, take part into the circuit of olfactory memory (Haberly and Bower, 1989;Calu et al, 2007;Sevelinges et al, 2007Sevelinges et al, , 2008. According to the alimentary status of animals, mitral cells of OB present increased activity in response to an odor associated to toxicosis (Pager and Royet, 1976).…”
Section: An Effective Cs-us Association Duringmentioning
confidence: 99%
“…COA is supported by a basic network, including olfactory areas, the basolateral amygdala, and the orbitofrontal cortex An increasing amount of findings show that the first stages of olfactory processing, the olfactory bulb and the piriform cortex, take part into the circuit of olfactory memory (Haberly and Bower, 1989;Calu et al, 2007;Sevelinges et al, 2007Sevelinges et al, , 2008. According to the alimentary status of animals, mitral cells of OB present increased activity in response to an odor associated to toxicosis (Pager and Royet, 1976).…”
Section: An Effective Cs-us Association Duringmentioning
confidence: 99%
“…These data further argue for the involvement of pPCx in odor fear conditioning and, more generally, in cognitive mnesic processes, including learning and recall of associations between odorants and information from other sensory modalities (Litaudon et al 1997(Litaudon et al , 2003Chabaud et al 1999Chabaud et al , 2000Mouly et al 2001;Mouly and Gervais 2002;Sevelinges et al 2004Sevelinges et al , 2008Mouly and Di Scala 2006;Jones et al 2007), while the anterior part of the piriform cortex is more involved in sensory processes and simple forms of memory, such as short-term habituation (Wilson 1998a(Wilson ,b, 2000Kadohisa and Wilson 2006), pattern completion (Barnes and Thomas 2008), and perceptual learning (Wilson and Stevenson 2003).…”
Section: Amino Acids Variations In Ppcxmentioning
confidence: 99%
“…Moreover, the BLA plays a major role in the acquisition, consolidation, and retention of olfactory fear conditioning (Cousens and Otto 1998;Rosenkranz and Grace 2002;Kilpatrick and Cahill 2003;Sevelinges et al 2004Sevelinges et al , 2007Walker et al 2005;Jones et al 2007), thus extending previous observations with auditory and visual CSs to include odor cues. Recent studies also suggest that the posterior piriform cortex (pPCx) may play a critical role in this associative learning (Sevelinges et al 2004(Sevelinges et al , 2008Jones et al 2007). Therefore, the olfactory system constitutes a particularly relevant model for studying the relative contribution of sensory cortices and amygdalar nuclei to odor fear learning.…”
mentioning
confidence: 99%
“…Recently, Luna and Morozov (2012) reported that the pPC differentially responds to amygdaloid versus cortical inputs by utilizing distinct local microcircuits. The pPC is thus an ideal locus to combine the sensory characteristics of the stimulus with its affective learned value transmitted by the BLA to keep the trace of this emotional olfactory memory as suggested by previous studies (Sevelinges et al 2004(Sevelinges et al , 2008(Sevelinges et al , 2011Barnes et al 2011;Chen et al 2011).…”
mentioning
confidence: 99%
“…Recently, Luna and Morozov (2012) reported that the pPC differentially responds to amygdaloid versus cortical inputs by utilizing distinct local microcircuits. The pPC is thus an ideal locus to combine the sensory characteristics of the stimulus with its affective learned value transmitted by the BLA to keep the trace of this emotional olfactory memory as suggested by previous studies (Sevelinges et al 2004(Sevelinges et al , 2008(Sevelinges et al , 2011Barnes et al 2011;Chen et al 2011).Most studies questioning the role of sensory cortices in fear conditioning have used auditory stimuli. These studies revealed that the lesion of auditory sensory cortices do not prevent the acquisition of auditory fear conditioning, thus arguing against their involvement in the learning (Campeau and Davis 1995; Armony et al 1997).…”
mentioning
confidence: 99%